Peningkatan Pengetahuan Digital Marketing Bagi UMKM Melalui Pemanfaatan Media Sosial - Chindy Clawdya Br Ginting; Yudas Tadius Andi Candra (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to expand the understanding of digital marketing among Micro, Small, and Medium Enterprises (MSMEs) by utilizing social media. In today's digital era, social media has become one of the effective channels for promoting products and services. Adequate knowledge of digital marketing strategies can support MSMEs in increasing their visibility and sales. The method applied in this study is through training and workshops involving digital marketing practitioners. The findings of this study indicate that participants experienced a significant increase in their understanding and application of digital marketing strategies through social media, as well as a positive impact on their business growth.